Design, Synthesis and Pharmacological Evaluation of Naphthofuran Derivatives as Potent SIRT1 Activators - Gao, Jian; Chen, Qing-Qing; Huang, Ye; Li, Kai-Hang; Geng, Xiao-Ju; Wang, Tao; Lin, Qi-Si; Yao, Ruo-Si (Frontiers in Pharmacology, 2021)
Diabetic nephropathy (DN) is one of the most important medical complications in diabetic patients, which is an essential cause of end-stage renal disease in diabetic patients and still lacks effective medicines. Silent information regulator 1 (SIRT1) is closely related to the occurrence and development of DN. Activation of SIRT1 could significantly improve the symptoms of DN, while the activities of SIRT1 activators need to be further improved. Based on the crystal structure of SIRT1, structure and ligand-based approaches were carried out, and a lead compound 4456-0661 (renamed as M1) was identified. Moreover, seven M1 analogues (6a-6g) were designed using a structure-based drug design strategy followed by bioactivity evaluation with SRTR2104 used as positive drugs. Among the target molecules, compounds M1, 6b, and 6d were proved to be potent SIRT1 activators, the activities of which are comparable to SRT2104. More importantly, compounds M1, 6b and 6d could resist high glucose-induced apoptosis of HK-2 cells by activating SIRT1 and deacetylation of p53. Apart from the beneficial effect on apoptosis of DN, these compounds also alleviated high glucose stimulating inflammation response in HK-2 cells through SIRT1/NF-κB(p65) pathway. Consequently, M1, 6b, and 6d could be promising drug candidates for SIRT1 related diseases.